2018
DOI: 10.1111/dom.13449
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of free fatty acids correlate with type 2 diabetes mellitus

Abstract: FFA levels are elevated in newly diagnosed and long-term controlled T2DM patients, providing high diagnostic accuracy of 87% and 91%, respectively, which improved further when combined with the glycation degree of lysine-141 in haptoglobin. Additionally, FFA showed higher mean fold-changes than HbA1c or FPG in subjects developing T2DM, indicating higher sensitivity towards the progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 59 publications
5
42
0
Order By: Relevance
“…An increase in FFAs was also observed in obese rats, confirming previous observations, not only in obesity but also in diabetes [25,26]. This accumulation could involve a higher FA uptake at both cellular and mitochondrial levels, as mentioned above due to increased lipid supply in obesity.…”
Section: Discussionsupporting
confidence: 90%
“…An increase in FFAs was also observed in obese rats, confirming previous observations, not only in obesity but also in diabetes [25,26]. This accumulation could involve a higher FA uptake at both cellular and mitochondrial levels, as mentioned above due to increased lipid supply in obesity.…”
Section: Discussionsupporting
confidence: 90%
“…This type of cellular “starvation” is covered by release of fatty acids from triglycerides which in turns results in higher NEFA concentrations [ 39 ]. On the other hand, for decades it has gained widespread acceptance that high concentrations of NEFAs can contribute to insulin resistance, e.g.by the toxic influence on pancreatic β-cells and thus impaired insulin secretion and peripheral sensitivity to insulin, and also by increasing activation of proinflammatory cytokines as well as oxidative stress [ 40 ]. Results obtained in this study indicated that the increase in circulating NEFAs in lung cancer patients was associated with elevated glucose concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The authors further recommend the measurement of serum FFA concentration in combination with existing diabetic diagonostic tools to improve the diagnostic accuracy. This study ranked the earlier diagnostic accuracy from the newly diagnosed diabetic patients to those monitored for a long time [132]. Yi et al [133] demonstrated both esterified and non-esterified FA to screen the DM patients from healthy ones.…”
Section: Biomarkers Of Disturbed Lipid Metabolismmentioning
confidence: 92%